Sustainable rural tourism development at Gunung Stong State Forest Park (GSSFP) from the perspective of external tourism stakeholders - Liew Wee Lun; Syaza Liyana Rosli; Nur Adilah Ali; Syuhada Farhana Adnan (2016)
Industrial tourism in Malaysia plays an important role in improving the country's economy. Accordingly, the government often takes a serious view on the development of this sector and it was always been debated in the parliament. State tourism sector is now the sixth largest contributor to the country's economy by contributing a total of RM161 billion or 14.9 percent of the Gross Domestic Product (GDP). Tourism in Kelantan especially still in a low level of standard because there are many destinations that could potentially be used as a tourist destination but not yet fully developed and commercialized. The objectives of this research are to determine the potential of sustainable rural tourism development at Gunung Stong State Forest Park (GSSFP), Kelantan from the perspective of tourism external stakeholders. Besides that, the objectives also want to know the level of external stakeholder support towards the development of GSSFP, Kelantan. Besides that, this research also aims to identify the impact of the sustainable rural tourism development at GSSFP, Kelantan. The research methods that have been used are interview with application of coding methods. Through the study, GSSFP had a potential to become a top tourists destination in the world in terms of eco-tourism sector. For future research, researchers are expected to include other aspect that involve community participation and local businesses that may influence the development of GSSFP.